Creativity in biology: The impact of Problem-Oriented Project Based Learning on high school students - Ria Novita Ayu Komalasari; I. Ibrohim; Dwi Listyorini (University of Muhammadiyah Malang, 2024)
Creativity in biology education is a crucial aspect that enhances students’ understanding of the subject. It consists of several indicators (fluency, flexibility, originality, and elaboration), which can also be used as measuring tools for creativity. This study aimed to determine the influence of the Problem-Oriented Project-Based Learning (POPBL) model in fostering creativity among high school students. The experiment was conducted in April until June 2023. The participants of this study consisted of 10th-grade students from State High School 1 Grogol. The cluster random sampling technique selected X6 as the control and X7 as the experimental classes. This was a quasi-experiment with a Pretest-Posttest Control Group Design, in which two groups were chosen randomly where the classes had previously been tested for equality first. The analysis employed was an analysis of the covariance test. The statistical analysis revealed that students’ creativity in the experimental group was significantly higher than in the control group. Based on this study, we conclude that the POPBL model significantly improved student creativity. We suggest that with higher creativity, students will be able to solve the problems they face in life better.